1993
DOI: 10.1007/bf01379086
|View full text |Cite
|
Sign up to set email alerts
|

DNA homology in species of bacteriophages active onPseudomonas aeruginosa

Abstract: Using electron microscopy and DNA-DNA-hybridization, 113 virulent and temperate bacteriophages specific for P. aeruginosa have been assigned to 23 species. In most cases, especially in virulent phages, both particle morphology and DNA homology types were in good correlation and their use was sufficient for clear-cut definition of phage species. No virulent phages of different species had any DNA homology. DNA homology was detected between temperate phages of several species. Temperate phages formed two large g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…S2 in the supplemental material). As was the case for other authors, DNA homology was not observed among phages belonging to different morphological families (4,26,28,44). Therefore, 12 species were identified among the 65 dsDNA phages analyzed: 2 Myoviridae, 9 Siphoviridae (4 of which harbored nonrestrictable DNA), and 1 Podoviridae species (Table 1).…”
Section: Because They Have Different Host Ranges (See Below)supporting
confidence: 66%
See 2 more Smart Citations
“…S2 in the supplemental material). As was the case for other authors, DNA homology was not observed among phages belonging to different morphological families (4,26,28,44). Therefore, 12 species were identified among the 65 dsDNA phages analyzed: 2 Myoviridae, 9 Siphoviridae (4 of which harbored nonrestrictable DNA), and 1 Podoviridae species (Table 1).…”
Section: Because They Have Different Host Ranges (See Below)supporting
confidence: 66%
“…These virulent myoviruses are distributed globally and have a broad host range, using the cell lipopolysaccharide layer as their primary receptor (25). No fewer than 42 phages of this species have been isolated and identified across Europe (28,37); this result evidenced its presence in Mexico. A second myovirus species in our collection was represented by PaMx12 (Table 1).…”
Section: Because They Have Different Host Ranges (See Below)mentioning
confidence: 82%
See 1 more Smart Citation
“…Phages of the ϕ KZ family have been used as components of therapeutic formulations for a long time [11][12][13], because many of them infect P. aeruginosa strains resistant to other phages [14] as well as some Burkhodleria cepacia strains (our observations). The intracellular development of numerous ϕ KZ-like phages often takes place in the presence of P. aeruginosa plasmids that suppress the growth of phages of other species [15].…”
Section: Introductionmentioning
confidence: 84%
“…Abundance of different phage species active on P. aeruginosa [13] with more than 80 different phages with sequenced genomes available in NCBI database [14] confirms the possibility for choosing the active phages.…”
Section: P Aeruginosa Virulent ("Lytic") Bacteriophagesmentioning
confidence: 98%